2012
DOI: 10.1097/mlr.0b013e3182290349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bariatric Surgery on Health Care Utilization and Costs Among Patients With Diabetes

Abstract: Background The effect of bariatric surgery on health care utilization and costs among individuals with type 2 diabetes remains unclear. Objective To examine healthcare utilization and costs in an insured cohort of individuals with type 2 diabetes after bariatric surgery. Research Design Cohort study derived from administrative data from 2002–2008 from 7 Blue Cross Blue Shield Plans. Subjects 7,806 individuals with type 2 diabetes who had bariatric surgery Measures Cost (inpatient, outpatient, pharmacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 26 publications
(25 reference statements)
3
40
1
Order By: Relevance
“…In the only three studies that monitored patients for a longer period, the results were not consistent [12,17,19]. According to Narbro et al (2002), although it was possible to reduce drug costs for DM and cardiovascular disease through surgical treatment, there was increased use of drugs for treating anemia, vitamin deficiencies, and gastrointestinal disorders and higher associated drug costs [12].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the only three studies that monitored patients for a longer period, the results were not consistent [12,17,19]. According to Narbro et al (2002), although it was possible to reduce drug costs for DM and cardiovascular disease through surgical treatment, there was increased use of drugs for treating anemia, vitamin deficiencies, and gastrointestinal disorders and higher associated drug costs [12].…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies identified comorbidity resolution as the main reason for bariatric surgery [3,8,16,17]. In the studies selected for this analysis, we observed that the comorbidities evaluated were not homogeneous ( Table 2).…”
Section: Comorbidities and Drug Use Before And After The Surgical Promentioning
confidence: 95%
See 1 more Smart Citation
“…Gastric banding led to 0.94 life-years gained, 1.34 QALYs gained and a cost-effectiveness ratio of $13,000/QALY. Bleich et al examined healthcare utilization and costs in 7806 individuals with Type 2 diabetes over 6 years after bariatric surgery [71], and reported no reduction in healthcare costs compared with before surgery. The ratio of hospital costs post surgery compared with presurgery was higher in years 2 to 6 after surgery and increased over time (1 year …”
Section: Cost-effectiveness Of Bariatric Surgerymentioning
confidence: 97%
“…Studies evaluating the longer-term health care costs have shown mixed results. [4][5][6] The study in this issue of JAMA Surgery by Lewis et al 7 brings important new data to this debate. Using a unique data source, private payer claims from across the United States, the authors were able to measure health care expenditures (from the payer perspective) over time for patients undergoing laparoscopic adjustable gastric banding and laparoscopic gastric bypass procedures.…”
mentioning
confidence: 99%